Checklist of Fish Specimens in the Zoological Museum of Institute for Biodiversity (IBD), Bukit Rengit, Lanchang, Pahang of Department of Wildlife and National Parks (DWNP) - Jeffrine Japning, Rovie-Ryan; Edward, Marilyn-Jaoi; Saharuddin M., Nazri; Sivananthan, Elagupillay (Department of Wildlife and National Parks, 2008)
The museum fish collection has a total of 437 specimens of freshwater fishes from 13 orders and families. A total of 76 valid species was listed, encompasses of 16.5% and 24.9% of the total fish species known to Malaysia and Peninsular Malaysia, respectively. 70 species are native to Malaysia, three are introduced (Barbonymus gonionotus, Oreochromis mossambicus, and Betta splendens), and one reintroduced (Trichogaster pectoralis). Clarias batu is listed as endemic while the native status of two species (Coilia nasus and Mystus vittatus) is questionable as both species are not listed as indigenous to Malaysia.